The characteristics of gmchi gene isolated from soybean cultivars with different isoflavone content - Hong Trang, Le Thi; Tuong, Ho Manh; Thanh Van, Tran Thi; Tung, Pham Thanh; Son, Le Van; Mau, Chu Hoang (Academia Journal of Biology, 2016)
In this study, isoflavone content of five soybean varieties disseminated grown in North Vietnam have been surveyed, and the GmCHI gene encoding chalcone isomerase, a key enzyme in metabolizing synthetic isoflavone in soybeans, was analyzed. Content of isoflavone (daidzein, genistein) in 3-day-old germinated seeds of soybean cultivar DT26 was the highest (64.27 mg/100g) and higher 2.18 times and 2.45 times compared with DT84 and DT2008 respectively. GmCHI gene isolated from mRNA of the soybean cultivars DT26, DT51, DT2008, DT84 is 657 nucleotides in length, encoding 218 amino acids. Similarity coefficient of nucleotide sequence of GmCHI gene of four soybean DT26, DT51, DT2008, DT84 ranged from 96.8% to 98.9% and similar to those of NM_001248290 on GenBank from 98% to 99%. Genetic distances of DT26 compared with DT51 DT26, DT2008, DT84 and other varieties based on nucleotide sequences of GmCHI gene was 19.3% and based on the amino acid sequence deduced was 4.4%. Coding region of GmCHI gene has been used as a material for design transfomation vector for the improvement of isoflavone content in soybean by gene transfer technique.